Analisis User-Experience: Limitasi Pemain Pada Hybrid Reality Games (HRG) Pokemon Go - Jessica, Elizabeth (UNIVERSITAS NUSA PUTRA, 2024)
Pokemon Go (PG) became a phenomenon at the time of release in 2016. It was one of the first case studies of a game that provides the masses with a hybrid reality game experience (HRG) which has the element of mobility, sociability, and spatiality. This research aims to study the design elements, motivation, experience, and how HRG might limit experience in playing the game. The study benefits from data from media studies, previous research, and interviews with users and game designers. The research shows familiarity with the name, advertisement and social media sharing, social influence, and the new technology gave motivation to play the game. While in user experience, the main purpose of playing the game is to finish the goal, completing all of the pokemon, and some of the reasons for the abandonment are travel issues and lack of update from the developer. Two of the elements of HRG, mobility and spatiality are linked as the reasons for players' frustrations and difficulties. They found it hard to travel or explore around to search for pokemon and could only catch pokemon in a limited area. Players also reported they did not explicitly travel to search for pokemon, but instead will play when they are travelling for other things.